KAJIAN METODE SEO BERBASIS ON-PAGE SEBAGAI STRATEGI MENINGKATKAN VISIBILITAS WEBSITE DI SERP - Nizar Haris Masruri (Universitas Palangka Raya, 2022)
The business sector in industry 4.0 always depends on the development of internet technology, one of which is a website. Website is a medium of business information that serves to expand marketing in order to reach users all over the world. The success of a website is when it is in the top position in the SERP (Search Engine Result Page). Until now, new websites have sprung up that make the competition even tougher. Therefore, we need a method to improve the quality of the website in order to be able to compete with other websites. One of the efforts to improve the quality of the website is to optimize the website structure using the On-Page SEO method. SEO (Search Engine Optimization) is an effort to optimize the performance and quality of a website so that it is prioritized by search engines. While On-Page SEO is an optimization process carried out on the website structure. On-page is a fundamental process that must be done in building a quality website. For this reason, this article will discuss how to design a quality website structure using the On-Page SEO method which is expected to be a benchmark for the quality of the website structure that will be built by readers.